Incidence of Pressure Injuries in Patients at Risk Using a Powered Alternating Pressure Air Mattress: A Noninterventional Study in a Real-World Setting - Meaume, Sylvie; Urbinelli, Renaud; Marty, Marc (Journal of wound, ostomy, and continence nursing, 2024)
The aim of the study was to determine the clinical value of using a powered alternating pressure air mattress (P-APAM) in the prevention of pressure injury (PI) in patients at medium to high risk. Noncomparative, observational study. The sample comprised 86 patients who were >18 years old, were classified as having medium to high risk of PI, had no PI at baseline, and were lying more than 15 hours a day on a specific P-APAM. Data were collected between September 2018 and July 2019, in 4 nursing homes, and 1 long-term care geriatrics hospital department in France. In addition to guideline-based care for PI prevention, patients were followed up for 35 days following placement on the P-APAM. The main outcome was the percentage of patients who developed between day 0 and day 35 at least 1 PI of at least stage 2 on the sacrum, spine, or heel. Secondary outcomes were patient assessments of comfort, caregiver satisfaction, mattress noise level, and mattress safety. No patients experienced a PI (incidence = 0%; 95% confidence interval, 0.00%-4.28%). Patients were satisfied or very satisfied with the mattress in most cases in terms of comfort (77.9%) and stability (73.0%). Patients also rated the noise level of the mattress as satisfactory or very satisfactory in all cases (100%). When combined with guideline-based PI prevention measures, use of the P-APAM was associated with a low incidence of PI.